2013
DOI: 10.1093/nar/gkt1301
|View full text |Cite
|
Sign up to set email alerts
|

Promoter occupancy of the basal class I transcription factor A differs strongly between active and silent VSG expression sites in Trypanosoma brucei

Abstract: Monoallelic expression within a gene family is found in pathogens exhibiting antigenic variation and in mammalian olfactory neurons. Trypanosoma brucei, a lethal parasite living in the human bloodstream, expresses variant surface glycoprotein (VSG) from 1 of 15 bloodstream expression sites (BESs) by virtue of a multifunctional RNA polymerase I. The active BES is transcribed in an extranucleolar compartment termed the expression site body (ESB), whereas silent BESs, located elsewhere within the nucleus, are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…The occupancy by this factor and RNA pol I was several times higher in the first few hundred base pairs of the active ES than in the equivalent region of a silent ES. However, significant CITFA occupancy also was found on silent ESs (43,44). Thus, these analyses, together with the results presented herein, allow us to claim that transcription initiation is not the determinant level of ES control.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The occupancy by this factor and RNA pol I was several times higher in the first few hundred base pairs of the active ES than in the equivalent region of a silent ES. However, significant CITFA occupancy also was found on silent ESs (43,44). Thus, these analyses, together with the results presented herein, allow us to claim that transcription initiation is not the determinant level of ES control.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, the active expression site is uniquely devoid of nucleosomes (9, 10), probably favoring transcription elongation and correlating with a higher occupancy by RNA pol I and RNA pol I transcription factor at the beginning of the active ES (44). Also, rates of transcript processing and cytoplasmic export and stability are different in transcripts of the active and inactive ESs (29).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that some transcripts can in fact be detected from silent BES, even in the absence of the above perturbations, suggests that selective RNA Pol I elongation may be the key (100). However, other studies have shown that RNA Pol I occupation levels are higher at the promoter of the active BES, suggesting that selective transcription initiation may also contribute (101).…”
Section: The Genomic Components Of Antigenic Variation In Trypanosomamentioning
confidence: 90%
“…This monoallelic VSG expression ensures that after a VSG switching event, the originally active VSG no longer is expressed on the cell surface. Several mechanisms of VSG expression regulation have been identified, including specialized localization of the active ES at an extranucleolar ES body (ESB) that is enriched with RNA polymerase I (24), regulated transcription elongation along ESs (25,26), modulation of ES chromatin structure (27)(28)(29)(30)(31)(32), modulation of ES promoter activities (33)(34)(35)(36)(37), and telomere protein-mediated telomeric silencing (38,39). VSG expression regulation has been reviewed elsewhere recently (40, 41) and will not be discussed here in detail.…”
Section: Antigenic Variation In T Bruceimentioning
confidence: 99%